Mentors' and mentees' intellectual-partnership through the lens of the Transformative Learning Theory. (July 2017) - Zanchetta, Margareth Santos; Bailey, Annette; Kolisnyk, Olesya; Baku, Lorena; Schwind, Jasna; Osino, Eunice; Aksenchuk-Metersky, Kateryna; Mehari, Niyat; Babalola, Oluwafunmbi; Christopher, Joneet; Hassan, Aafreen; Leong, Newton; et al.
Abstract: In this paper we report reflections about the scholarly mentoring experiences of undergraduate nursing students (mentees) and faculty members (mentors) involved in an intellectual partnership at a Canadian university. The paper specifically recounts the impacts of the transformative process experienced by 18 mentees and three mentors, based on their in-depth written critical reflections. In this collaborative initiative, the constructivist framework of Shor and Freire, and Mezirow's Transformative Learning Theory, served as foundations for all interactions between mentees and mentors, and guided the analysis and interpretation of their written self-reflections. Mentees and mentors were motivated by complementary goals for the intellectual relationships. Their combined contexts, self-reflective, critical dialogue, shared assumptions and ideas worked to ignite a critical awareness of their potential and self in their professional world. Sharing new ways of thinking and points of view stimulated their transformation on various levels –emotional, cognitive, and spiritual. Highlights: We examined an intellectual partnership between faculty and undergraduate students. Mentors and mentees experienced emotional, cognitive, and spiritual transformation. Learning and development had a renewed meaning for mentors and mentees. The mentorship led to mutually satisfying personal and professional development. Scholarly activities with mentees produced significant results.